Engineering a reagentless biosensor for single-stranded DNA to measure real-time helicase activity in Bacillus - Green, Matthew; Gilhooly, Neville S.; Abedeen, Shahriar; Scott, David J.; Dillingham, Mark S.; Soultanas, Panos (Elsevier, 2014)
Single-stranded DNA-binding protein (SSB) is a well characterized ubiquitous and essential bacterial protein involved in almost all aspects of DNA metabolism. Using the Bacillus subtilis SSB we have generated a reagentless SSB biosensor that can be used as a helicase probe in B. subtilis and closely related gram positive bacteria. We have demonstrated the utility of the probe in a DNA unwinding reaction using a helicase from Bacillus and for the first time, characterized the B. subtilis SSB's DNA binding mode switching and stoichiometry. The importance of SSB in DNA metabolism is not limited to simply binding and protecting ssDNA during DNA replication, as previously thought. It interacts with an array of partner proteins to coordinate many different aspects of DNA metabolism. In most cases its interactions with partner proteins is species-specific and for this reason, knowing how to produce and use cognate reagentless SSB biosensors in different bacteria is critical. Here we explain how to produce a B. subtilis SSB probe that exhibits 9-fold fluorescence increase upon binding to single stranded DNA and can be used in all related gram positive firmicutes which employ drastically different DNA replication and repair systems than the widely studied Escherichia coli. The materials to produce the B. subtilis SSB probe are commercially available, so the methodology described here is widely available unlike previously published methods for the E. coli SSB.